NUDT21 lactylation reprograms alternative polyadenylation to promote cuproptosis resistance - Jinlong Lin; Yixin Yin; Jinghua Cao; Yiyang Zhang; Jiewei Chen; Rixin Chen; Bingxu Zou; Cijun Huang; Yongrui Lv; Shuidan Xu; Han Yang; Peng Lin; et al. (Cell Discovery)
Abstract Alternative polyadenylation (APA) is critical for shaping transcriptome diversity and modulating cancer therapeutic resistance. While lactate is a well-established metabolic signal in cancer progression, its role in APA regulation remains unclear. Here, we demonstrate that l-lactate-induced lactylation of NUDT21 drives transcriptomic reprogramming through APA modulation. NUDT21 lactylation enhances its interaction with CPSF6, facilitating CFIm complex formation and inducing 3′ untranslated region (UTR) lengthening of FDX1. Extension of the FDX1 3′ UTR attenuates its protein output, thereby conferring resistance to cuproptosis in esophageal squamous cell carcinoma (ESCC). Furthermore, we identify AARS1 as the lactylation “writer” catalyzing NUDT21 K23 lactylation, and HDAC2 as its enzymatic “eraser”. Clinically, elevated levels of both LDHA and NUDT21, as well as increased K23-lactylated NUDT21, are associated with reduced FDX1 expression and worse prognosis in ESCC patients. Notably, combined targeting of the lactate-NUDT21-FDX1-cuproptosis axis with the clinical LDHA inhibitor stiripentol and the copper ionophore elesclomol synergistically suppressed tumor growth. Collectively, our work identifies lactylated NUDT21 as a critical factor linking cellular metabolism to APA and proposes a promising therapeutic strategy for ESCC treatment.